An unusual cause for globus sensation: infected tracheal diverticulum with abscess formation. Issue 2 (25th February 2022) - Leedman, S; Quick, M; Coombs, A; Hee, G
Abstract: Case report: A 43-year-old woman presented with a 3-week history of globus sensation and malaise. A computed tomography scan of her neck showed a large right paratracheal abscess secondary to an infected tracheal diverticulum. The patient was admitted under the ENT surgical team, and underwent incision and drainage of the abscess. There were no post-operative complications and she was discharged home after 2 days, on oral antibiotics. Conclusion: This case demonstrates that a tracheal diverticulum may become infected and present as a cervical abscess. To our knowledge, this is the fourth reported case in the international literature of abscess formation related to an infected tracheal diverticulum.